OVERNIGHT STOCK PRICE REVERSALS - KUDRYAVTSEV, Andrey (Journal of Advanced Studies in Finance, 2012)
In present study, I explore the dynamics of stock price reversals. In particular, I try to shed light on the overnight reversals, that is, on the price reversals between the end of a trading day and the opening session of the next trading day. To account for the "end-of-the-day" price moves, for each of the stocks currently making up the Dow Jones Industrial Index, I compare, on the daily basis, the high-to-close and the low-to-close price changes, and also compare them to the same day's average and median changes for the total sample of stocks. I document that opening returns tend to be higher following the days with relatively large high-to-close price changes (price decreases at the end of the day), and lower following the days with relatively large low-to-close price changes (price increases at the end of the day). Such "overnight reversals" price behavior seems to contradict the market efficiency. Finally, I construct five portfolios based on the opening trading sessions and involving a long position in the stocks on the days when, according to the "overnight reversals" behavior, their opening returns are expected to be high and a short position in the stocks on the days when their opening returns are expected to be low. All the portfolios are found to yield significantly positive returns, providing an evidence for the practical applicability of the "overnight reversals" pattern in stock prices.